Community-level determinants of loneliness and social isolation: a population-based cohort study across younger and older adults - Meehan, Drew Eleanor; Clare, Philip; Grunseit, Anne; Merom, Dafna (Frontiers in Public Health, 2025)
IntroductionLoneliness and social isolation (SI) are critical public health issues with well-documented effects on health and well-being. However, much of existing observational and intervention research has focused predominantly on individual-and interpersonal-level factors. This longitudinal study addresses significant knowledge gaps by comprehensively examining the independent influence of multiple community-level determinants on loneliness and SI and uniquely comparing these effects across younger (18–30 year) and older (60 + years) adults within an Australian population cohort over a 12-year period.MethodsUsing longitudinal data from the Household, Income and Labour Dynamics in Australia (HILDA) survey, we analysed data from four wave pairs (2006/07, 2010/11, 2014/15, 2018/19) to investigate associations between loneliness and SI and nine community and neighbourhood-level variables. We employed lagged mixed-effects Poisson regression models to calculate risk ratios (RR) adjusted for individual-and interpersonal-level factors.ResultsOur findings reveal that low community engagement is the strongest risk factor for loneliness and SI in both younger (Loneliness, RR = 1.34; SI, RR = 1.58) and older populations (Loneliness, RR = 1.35; SI = 2.02). Low neighbourhood social cohesion was found to significantly increase loneliness and SI in older adults (Loneliness, RR = 1.15; SI, RR = 1.36) and to increase SI in younger adults (RR = 1.54). We also observed distinct age-specific effects, with cultural practices, altruism, and perceived neighbourhood safety having differential impacts across age groups.DiscussionOur findings highlight the critical need for community-level interventions to address loneliness and SI, suggesting that focusing solely on individual-related factors is insufficient. Tailoring public health strategies to enhance community dynamics may be essential in reducing loneliness and SI among vulnerable populations, particularly in areas with low social cohesion and community engagement offerings.